NILAI-NILAI PENDIDIKAN KARAKTER DALAM CERPEN DALAM BUKU TEKS BAHASA INDONESIA SMP KELAS VII TERBITAN ERLANGGA TAHUN 2013 - Aliska Wulandari; Kamaruddin ,; Albertus Sinaga (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2016)
ABSTRACT The purpose of this study is to describe the values ​​of character education and the way the author describes the value of character education contained in the short story in the textbook of Indonesian SMP class VII Erlangga published in 2013. This research using qualitative methods and objective approach. The thing that is described is the value of character education and the way the author describes the value of character education in the short story in the textbook of Indonesian class VII class VII Erlangga year 2013. The data in this study in the form of educational values ​​of characters in the short story. Sources of data in this study are all short stories contained in textbooks of Indonesian SMP class VII Erlangga published in 2013. The data were analyzed tested the validity of the data with content analysis techniques and checks with triangulation theory theory. The results of this study found the value of character education consisting of : religious, honest, tolerant, disciplined, hard work, creative, independent, democracy, curiosity, respectful achievement, friendly / communicative, peace loving, caring environment, social care, and responsibility of the whole short story contained in the language text book Indonesia class VII Erlangga published in 2013. The way the author reflects the value of character education is in terms of characterization by direct means of direct and indirect description that is through the image of the physical and behavior of the character, the talk of other figures and responses of other figures in the short story tersebut.Hasil this study suggested, can help the teacher in choosing the material in character study and the results of this study can contribute thoughts and benefits for further researchers, especially those who review the value of education karekter. Keywords: values, character education, short stories, and textbooks